Reflections on Some of the Exceptional Features of HTLV-1 and HTLV-1 Research: A Perspective - Gallo, Robert C.; Tagaya, Yutaka (Frontiers in Immunology, 2022)
The report is not a review nor a summary. In a manner, it is a perspective but an unusual one. It looks back to the years my colleagues and I began preparing for human retroviruses (beginning in 1970), how they evolved, and attempts to bring to light or simply to emphasize many exceptional characteristics of this virus and some fortuitous coincidences, and with emphasis on the needs of the field. These events cover over one half a century.